2023
DOI: 10.3390/atmos14121706
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Evaluation of the Efficiency of an Indoor Air Cleaner under Different Heating Conditions

Andrejs Sabanskis,
Dagis Daniels Vidulejs,
Jevgēnijs Teličko
et al.

Abstract: For an efficient indoor air purification, it is important to know the detailed airflow distribution in the room. A series of numerical simulations are carried out for five heating regimes using an air–air heat pump, capillary mat on the ceiling, capillary mat on the walls, heated floor, and radiator. The most homogeneous temperature field is obtained for the case with the heated floor. The highest velocity is obtained for the air–air heat pump, while the lowest is obtained for the capillary mat on the ceiling.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Based on the transient observations presented so far, we can derive several correlations and interactions between various effects discussed in this section. Our results mainly confirm the findings of investigations conducted by other authors (see [14][15][16][17][18]21,22]), we also show that an air purifier leads to a significant reduction in the aerosol concentration in the room air. We extend the existing knowledge by highlighting the additional impact of transient, intermittent window ventilation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Based on the transient observations presented so far, we can derive several correlations and interactions between various effects discussed in this section. Our results mainly confirm the findings of investigations conducted by other authors (see [14][15][16][17][18]21,22]), we also show that an air purifier leads to a significant reduction in the aerosol concentration in the room air. We extend the existing knowledge by highlighting the additional impact of transient, intermittent window ventilation.…”
Section: Discussionsupporting
confidence: 92%
“…They observed an overall reduction in the infection risk in all investigated scenarios where the air purifier was active, although zones with high local concentrations were found. Assuming different heating settings in a small chamber, Sabanskis et al [16] confirmed the strong sensitivity of the filtering efficiency of a mobile air purifier to the positions of both the aerosol source and the filtration device. Duill et al [17] conducted a thorough study to investigate a classroom setting using different air purifier types, with one type operated at two different locations.…”
Section: Introductionmentioning
confidence: 95%
“…However, if this is not feasible, Küpper et al showed that placing APs in the corner of a room is still effective if there is no disturbance for the air flow at the intake and outlet [37]. Aerosol spreading has also been described numerically to spatially resolve aerosol spreading, i.e., for a more precise evaluation of room mixing, prediction of infection risk, or the optimized positioning of filtering devices [38][39][40][41][42][43]. Most of these considerations mainly cover unsteady situations.…”
Section: Introductionmentioning
confidence: 99%